2008
DOI: 10.1111/j.1742-4658.2008.06722.x
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of zebrafish hatching enzyme – an evolutionary aspect of the mechanism of egg envelope digestion

Abstract: Hatching enzyme is an enzyme that digests an egg envelope at the time of embryo hatching. Fish hatching enzymes have been purified from several fish species [1][2][3][4][5]. Among them, the hatching enzyme of medaka Oryzias latipes has been extensively studied, and its study field was extended not only to characterization of the enzyme itself, but also to the mechanism of its egg envelope digestion [6,7]. The hatching of There are two hatching enzyme homologues in the zebrafish genome: zebrafish hatching enzym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
88
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 105 publications
(94 citation statements)
references
References 30 publications
5
88
0
1
Order By: Relevance
“…3), consistent with the previously reported cleavage efficiency difference. 6 Alanine-scanning mutagenesis of the most preferable 10-residue substrate (TVQQS↓DYLIK, the major substrate peptide or WT-major) has shown that the Asp-to-Ala mutation at P1′ decreases the cleavage efficiency to 3.9% that of the original substrate. On the other hand, the mutation at P5′ increases the cleavage efficiency to 128%.…”
Section: Zinc-binding and Substrate-binding Sites Of Zhe1mentioning
confidence: 99%
See 3 more Smart Citations
“…3), consistent with the previously reported cleavage efficiency difference. 6 Alanine-scanning mutagenesis of the most preferable 10-residue substrate (TVQQS↓DYLIK, the major substrate peptide or WT-major) has shown that the Asp-to-Ala mutation at P1′ decreases the cleavage efficiency to 3.9% that of the original substrate. On the other hand, the mutation at P5′ increases the cleavage efficiency to 128%.…”
Section: Zinc-binding and Substrate-binding Sites Of Zhe1mentioning
confidence: 99%
“…The major site is cleaved three times more efficiently than the minor site, and is also cleaved four times more efficiently than the most preferable MCA substrate reported, N-benzyloxycarbonyl-Phe-Arg-MCA. 6 These differences in cleavage efficiency suggest that ZHE1 recognizes both the amino acid sequence and the conformation of the substrate. Two other zinc metalloproteases that are related to ZHE1 in amino acid sequence-astacin and bone morphogenetic protein 1 (BMP1)-exhibit different substrate preferences from ZHE1.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[47] The hatching process in zebrafish is initiated by the release of a protease, zebrafish hatching enzyme (ZHE1), into the embryonic fluid, and it culminates with zebrafish movements physically disrupting the ZHE1 weakened chorion. [171] Although Ong et al [47] observed no effect on the movement of hatched larvae, ZnO NMs inhibited protease activity in isolates of chorionic fluid extracted from zebrafish embryos in vitro. This specific inhibition of ZHE1 by ZnO NMs has also been further elucidated since by Lin et al [172] who reported the in vitro inhibition of the proteolytic activity of recombinant ZHE1 expressed in Escherichia coli.…”
Section: Zinc Oxide Nmsmentioning
confidence: 99%